The use of essential oil embedded in polylactic acid/chitosan-based film for mango post-harvest application against pathogenic fungi - Gunny, Ahmad Anas Nagoor; Leem, Siew Juan; Makhtar, Muaz Mohd Zaini; Zainuddin, Nor’izzah; Mohd Roslim, Muhammad Huzaifah; Raja Hashim, Raja Hasnida; Pusphanathan, Kavita; Siddiqui, Masoom Raza; Alam, Mahboob; Rafatullah, Mohd (Multidisciplinary Digital Publishing Institute, 2023)
Mango has a high global demand. Fruit fungal disease causes post-harvest mango and fruit losses. Conventional chemical fungicides and plastic prevent fungal diseases but they are hazardous to humans and the environment. Direct application of essential oil for post-harvest fruit control is not a cost-effective approach. The current work offers an eco-friendly alternative to controlling the post-harvest disease of fruit using a film amalgamated with oil derived from Melaleuca alternifolia. Further, this research also aimed to assess the mechanical, antioxidant, and antifungal properties of the film infused with essential oil. ASTM D882 was performed to determine the tensile strength of the film. The antioxidant reaction of the film was assessed using the DPPH assay. In vitro and in vivo tests were used to evaluate the inhibitory development of the film against pathogenic fungi, by comparing the film with different levels of essential oil together with the treatment of the control and chemical fungicide. Disk diffusion was used to evaluate mycelial growth inhibition, where the film incorporated with 1.2 wt% essential oil yielded the best results. For in vivo testing of wounded mango, the disease incidence was successfully reduced. For in vivo testing of unwounded mango to which the film incorporated with essential oil was applied, although some quality parameters such as the color index were not significantly affected, weight loss was reduced, soluble solid content was increased, and firmness was increased, compared to the control. Thus, the film incorporated with essential oil (EO) from M. alternifolia can be an environmentally friendly alternative to the conventional approach and the direct application of essential oil to control post-harvest disease in mango.